Model of the Connecting Optimal Number of Heat Consumers - Sergey M. Terekhov; Vladimir A. Nemtinov; Kirill S. Kornilov (Моделирование и анализ информационных систем)
In the modern world, the efficient use of energy is an extremely important aspect of human activity. In particular, heat supply systems have significant economic, environmental and social importance for both heat consumers and heat supply organizations. The economic status of all participants in the heat supply process depends on the efficiency of the functioning of the heat supply systems. The reliability of the functioning of systems depends on vital processes such as the work of hospitals and industrial enterprises. With such a close network communication, reliable and efficient operation of power supply systems is critical. In this article, ways to improve the efficiency of heat supply systems are considered. A mathematical model for improved planning of heat supply systems by connecting the optimal set of new heat consumers is presented. For each single customer, when there is an alternative option for connecting this consumer to the existing heat network, it is possible to choose the only optimal solution. This becomes possible due to the restrictions and the procedure for selecting variants from a subset of binary variables corresponding to alternatives. The procedure for finding the optimal number of consumers for connection to the existing heat network is presented, which is the rationale for increasing the number of existing consumers of the heat network. The testing was carried out and the results of the mathematical model by an example of test heat networks are presented. Directions of further study of increasing the efficiency of heat supply systems and integrating the presented mathematical model with modern software complexes are determined.